SIMULATION BASED COMPARATIVE ANALYSIS FOR THE DESIGN OF LASER TERRESTRIAL MOBILE MAPPING SYSTEMS - YOO, HYUN-JAE; GOULETTE, FRANÇOIS; SENPAUROCA, JOEL; LEPÈRE, GREGORY (Boletim de Ciências Geodésicas, 2009)
Over the past decade, laser terrestrial Mobile Mapping Systems (MMS) have been developed for the digital mapping of outdoor environments. While the applications of MMS are various (urban security, road control, virtual world, entertainment, etc.), one may imagine that for each application the system designs could be different. Hence, a comparative analysis of different designs may be useful to find the best solution adapted to each application. The objective of this paper is to propose a methodology to compare point-cloud data quality from different MMS designs by modifying spatial configuration of laser imaging system. For this methodology, we define several quality criteria such as precision, resolution, completeness. We illustrate this in the case of urban architecture digital mapping based on the use of a simulator.